Incidence and risk for traumatic and overuse injuries in top-level road cyclists - de Bernardo, N.; Barrios, C.; Vera, P.; Laiz, C.; Hadala, M. (Journal of Sports Sciences, 2012)
All traumatic and overuse injuries occurring during an average period of 4 years (2002/09) in a group of 51 currently active road top-level cyclists were retrospectively registered through clinical interviews. Average age was 25.8 years. Average training and competition period was 28.3 ± 2.4 h a week. Only 8 cyclists (15.6%) were completely free from lesions during the period of study. The remaining 43 cyclists suffered a total of 112 lesions; however, 9 out of these were unrelated to their cycling practice. These 103 cycling-related injuries include 50 (48.5%) traumatic and 53 (51.5%) overuse injuries. Twenty-eight fractures were reported, the clavicle being the most frequently affected bone (11 cases). The 68.5% of overuse injuries were located in the lower limbs. Most overuse injuries (89.6%) occurred during the training period. According to the Injury Abbreviated Scale (AIS), severe lesions were only found in 4 cases (8% of traumatic injuries). Overall injury rates were 0.50 per racer/year, 2.02 per studied racer, and 0.007 per 1,000 km of training and competition. Active professional top-level cyclists are exposed to a high injury risk. According to the scarce previously published data the current study provides relevant information on the injury occurrence of still active top-level road cycling.